Efektivitas Teknik Diskusi Dalam Bimbingan Kelompok Untuk Meningkatkan Penyesuaian Diri Siswa (Jurnal Bimbingan dan Konseling Islam, 2016)
The study was carried out as a response to a problem faced by a student, teacher, class teacher and parent on a lack of fresh student’s self-adjustment competence in school circumstance. The student’s lack competence in adjusting him/herself, if it is ignored and not solved well, would affect their comfort in learning at school, resulting some consequences such as poor  learning achievement, dropping out and moving to new school.One of approaches  which can be done in improving student’s self adjustment is to serve group counseling through discussion technique. This study is aimed at revealing the effectiveness in improving student is self-adjustment. The theory refered to adjustment to school theory from Schneider and discussion technique from Bulatau. Pseudo-experiment with non-equivalent control group design was applied. The data then were analyzed with statistical non-parametric mann whitney and kolmogorov-semirnov.  The study shows that the depiction of students self-adjustment is in an average category, school choice which is determined by parents  becomes a quality background in students self-adjustment and discussion technique in group counseling in improving self-adjustment in showing  respect and applying teacher’s rule indicators. The recommendation of the study can be addressed to: 1) school management; the counseling service in improving student self-adjustment should be performed during first semester for student not from Taruna Bakti Junior High and empathy and corporation for student from Taruna Bakti Junior High. 2)  Counselors; a councelor can develop a personality aspect such as understand and do teachers’ rule with responsibility through group and  individual counseling service approach as usually happens in school circumstance. The approach can be one of solutions in eradicating self-adjustment problems. 3) Next researchers; the next researchers can consider parent-student communications in deciding school choice in improving the maturity of personality aspects in obtaining the quality of self-adjustment in school environment and for the researcher who is interested in the approach of discussion technique in next research is suggested that a group should be in one class (in-tack group), not from different classes.